2012
DOI: 10.3168/jds.2011-4298
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the sulfur hexafluoride tracer and respiration chamber techniques for estimating methane emissions and correction for rectum methane output from dairy cows

Abstract: The objectives of the present study were to compare the sulfur hexafluoride (SF₆) and respiration chamber techniques for measuring methane (CH₄) emissions from dairy cows and to determine the proportion of CH₄ that is released through the rectum. Data used were derived from 20 early lactation dairy cows in a 2 × 2 factorial design study for 4 periods with 6 wk/period. The 4 treatment diets consisted of grass silage and 2 levels of concentrate (30 and 60% dry matter basis), with or without yeast supplement. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 14 publications
1
44
0
2
Order By: Relevance
“…In ruminants, the vast majority of enteric CH 4 production occurs in the reticulo-rumen. Rectal emissions account for a marginal share of emissions (Murray et al, 1976;Muñ oz et al, 2012). A number of approaches, evaluated for mitigation of enteric CH 4 , are presented in Table 1.…”
Section: Mitigation Options For Enteric Methane Emissionsmentioning
confidence: 99%
“…In ruminants, the vast majority of enteric CH 4 production occurs in the reticulo-rumen. Rectal emissions account for a marginal share of emissions (Murray et al, 1976;Muñ oz et al, 2012). A number of approaches, evaluated for mitigation of enteric CH 4 , are presented in Table 1.…”
Section: Mitigation Options For Enteric Methane Emissionsmentioning
confidence: 99%
“…The use of a Latin square design in the present study reduces this effect of permeation tube release rate as all animals received all diets. Boadi et al (2002) and Muñoz et al (2012) reported that using the SF 6 technique resulted in a larger variation around the mean compared with chamber measurements, although measurements were not conducted simultaneously. However, it must be remembered that, despite its limitations, the SF 6 technique is still the only methodology that allows individual animal measurements under normal production systems (Lassey and Ulyatt, 2000).…”
Section: Feed Compositionmentioning
confidence: 99%
“…Pinares-Patiño et al 2008;Grainger et al 2010b;Muñoz et al 2012) or that the variance in methane yield measured by the original SF 6 technique was generally greater than the variance of methane yield measured by the chamber technique (Vlaming et al 2008;Hammond et al 2009Hammond et al , 2015.…”
Section: Improved Methodology For the Sf 6 Tracer Techniquementioning
confidence: 99%